Pengaruh Motivasi Belajar, Fasilitas Belajar dan Kepercayaan Diri terhadap Prestasi Belajar Mahasiswa Universitas Negeri Jakarta - Najwa Salsabila Putri; Marsofiyati Marsofiyati (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study aims to evaluate the influence of learning motivation, learning facilities, and self-confidence on the academic performance of students at Universitas Negeri Jakarta. Learning motivation is defined as the drive stemming from both internal and external factors that encourage academic success. Learning facilities refer to adequate infrastructure supporting learning activities, such as classrooms, libraries, and educational technology tools. Self-confidence reflects an individual’s belief in their own abilities to accomplish tasks and tackle academic challenges. This research uses a quantitative approach with a survey method, distributing questionnaires to 50 student respondents selected through probability sampling. Data was collected using a five-point Likert scale and analyzed through multiple linear regression to identify the relationships between the independent variables (learning motivation, learning facilities, and self-confidence) and the dependent variable (academic performance), measured by the Grade Point Average (GPA). The analysis results indicate that all three independent variables have a significant influence, both partially and simultaneously, on students' academic performance. Partially, learning facilities exert the most substantial influence, followed by self-confidence and learning motivation. This study suggests that educational institutions should focus on providing optimal learning facilities and supporting the development of student motivation and self-confidence to enhance academic performance.